Corruption risks and potential threats to the forestry sector in Peninsular Malaysia - Norsyazwani Izzati Mohd Yahya; Mohd Hasmadi Ismail; Pakhriazad Hassan Zaki; Paiman Bawon; Rahmawaty; Seca Gandaseca (Talenta Publisher, 2025)
Corruption and forest disturbances represent substantial barriers to sustainabledevelopment in Malaysia's forestry sector. Working within this sector faces avariety of threats. This study explores key corruption risks within the forestrysector, analysing the motives and opportunities that drive forest offences inPeninsular Malaysia. Respondents from relevant agencies were primarilysurveyed using questionnaires. Data analysis using SPSS revealed the corruptionrisks encountered within the forestry sector. Respondents identified fieldwork andreporting as potential areas susceptible to corruption, with their perceptionsanalyzed through central tendency and dispersion measures. Additionally,correlation analysis was conducted to determine the strength and direction of therelationship between motive and opportunity regarding forest offences, and toassess whether the correlation was statistically significant. The findingsdemonstrated a robust positive correlation (r = 0.66) between motive andopportunity, indicating a significant relationship. This suggests that motives forforest offences correspond to opportunities for such offences. This studyhighlights the need for targeted collaboration between the Forestry Departmentand relevant authorities to develop specialized training programs. These programsare crucial for effectively investigating and prosecuting forest violations,ultimately reducing corruption risks